ANALISIS RISIKO PADA PROSES PRODUKSI PABRIK TAHU KHARISMA - Failenggo, Ellent; Sumantika, Arsyad (Computer Science and Industrial Engineering, 2021)
Indonesia is one of the countries facing financial developments. Our nation is currently competing with other ASEAN countries to improve the economy in the modern region. The presence of the missing small and medium enterprises has made a tremendous contribution to the increase in the salaries of the Indonesian population. With abundant agricultural products, Indonesians have begun to take the initiative to increase the processed dishes from agricultural products.Failure Mode and Effect Analysis (FMEA) is one strategy to assess framework opportunities. FMEA can assess and dissect sections within the framework to limit the harm or impact of disillusionment levels as a supporting technique for assessing the framework's exhibits. The role of the FMEA method itself can be used to determine the risk of accidents in the production failure risk system, supply chain system risk components and so on. The prioritized risk assessment carried out at this stage is critical risk which has a high level of risk and a high RPN (risk priority number) score. . In future research, it is hoped that they will be able to implement and monitor and review the mitigation programs recommended in this study to be able to see the relevant mitigation proposals that can be applied by the company.